Management Practices for Methicillin-Resistant Staphylococcus aureus Bacteremia by Adult Infectious Diseases Physicians. (19th May 2018) - Banniettis, Natalie; Beekmann, Susan E; Polgreen, Philip M; Kaushik, Shubhi; Kohlhoff, Stephan; Gilbert, David; Bennett, John E; Hammerschlag, Margaret R
Abstract: To assess current use of vancomycin for methicillin-resistant Staphylococcus aureus bacteremia, we surveyed adult infectious disease physicians. Most respondents reported personal experience with infections failing to respond to vancomycin despite minimum inhibitory concentration data indicating susceptibility. In a hypothetical case of such an infection, most would change to daptomycin with or without other agents.